BUDAYA RELIGIUS DALAM MEMBANGUN INTEGRASI SOSIAL PESERTA DIDIK PADA SEKOLAH DASAR - Irianti, Indah Susi; Sigit Haryanto; Iim Fatimah; Umi Maghdhuroh; Djalal Fuadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of religious culture and analyze its role in building students’ social integration at SD Muhammadiyah Plus Semarang. This research was motivated by the importance of strengthening students’ social character amid increasing social problems such as low tolerance, social awareness, and cooperation in elementary school environments. This study employed a qualitative approach with a case study design. The research subjects consisted of the principal, teachers, and students selected through purposive sampling techniques. Data were collected through observation, semi-structured interviews, and documentation. Data validity was ensured through source and technique triangulation, while data analysis used the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings revealed that religious culture was implemented through religious habituation activities, teacher role modeling, and the creation of a religious school environment. The implementation contributed to the development of tolerance, cooperation, discipline, social awareness, and mutual respect among students. Religious culture also played a role in creating harmonious social relationships through collective activities that strengthened togetherness and social solidarity among students. This study confirms that religious culture not only functions to shape students’ spiritual character but also serves as a medium for internalizing social values in building students’ social integration in elementary schools.